STRATEGI IMPLEMENTASI KONSEP WATERFRONT CITY KOTA KUPANG (Implementation Strategy Of Waterfront Concept in Kupang City) - Setiadi, Amos (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, Kupang, 2018)
The vision of development of Kupang City is to develop is as the Centre of National Activities with sustainable waterfront city concept. It intends to solve problems resulting from the development of Kupang City seashore areas by orienting the development to establish seashore areas as the front gate of the city and avoiding construction of settlement building on riparian zones and seashore areas.bThe relevance of this vision is discussed using qualitative descriptive method based on data of the areas' profiles. The discussion concludes that Kupang City needs Detail Planning on Priority Areas' Spatial for riparian zones and seashore areas with development concept. Keywords: waterfront, sustainable, seashore, development concept